Evaluation of two lead malaria transmission blocking vaccine candidate antibodies in natural parasite-vector combinations - Bompard, A; Da, D; Yerbanga, R; Biswas, S; Kapulu, M; Bousema, T; Lefèvre, T; Cohuet, A; Churcher, T (Springer Nature, 2017)
Transmission blocking vaccines (TBV) which aim to control malaria by inhibiting human-to-mosquito transmission show considerable promise though their utility against naturally circulating parasites remains unknown. The efficacy of two lead candidates targeting Pfs25 and Pfs230 antigens to prevent onwards transmission of naturally occurring parasites to a local mosquito strain is assessed using direct membrane feeding assays and murine antibodies in Burkina Faso. The transmission blocking activity of both candidates depends on the level of parasite exposure (as assessed by the mean number of oocysts in control mosquitoes) and antibody titers. A mathematical framework is devised to allow the efficacy of different candidates to be directly compared and determine the minimal antibody titers required to halt transmission in different settings. The increased efficacy with diminishing parasite exposure indicates that the efficacy of vaccines targeting either Pfs25 or Pfs230 may increase as malaria transmission declines. This has important implications for late-stage candidate selection and assessing how they can support the drive for malaria elimination.